2023
DOI: 10.1155/2023/6893677
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Usutu Virus Africa 3 Lineage in a Survey of Mosquitoes and Birds from Urban Areas of Western Spain

Abstract: Usutu virus (USUV) is an emerging zoonotic arbovirus that has caused an increasing number of animal and human cases in Europe in recent years. Understanding the vector species and avian hosts involved in the USUV enzootic cycle in an area of active circulation is vital to anticipate potential outbreaks. Mosquitoes were captured in 2020, while wild birds were sampled in both 2020 and 2021 in Extremadura, southwestern Spain. The presence of USUV in the mosquito vectors was assessed by a real-time reverse transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Another study carried out in dogs in the southwest of Spain revealed the presence of neutralising antibodies against WNV and TBEV, demonstrating the circulation of these viruses in these areas ( García-Bocanegra et al., 2018 ). Moreover, the recent detection of USUV (RNA in mosquitoes and USUV-specific antibodies in birds) and an undetermined flavivirus highlights the widespread circulation of WNV in this endemic area and its co-circulation with USUV and other flaviviruses ( Bravo-Barriga et al., 2023 ). In the six patients studied in this work, cross-reactive IgG antibodies against USUV and TBEV were detected in all the convalescent sera samples tested, but not in the CSF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study carried out in dogs in the southwest of Spain revealed the presence of neutralising antibodies against WNV and TBEV, demonstrating the circulation of these viruses in these areas ( García-Bocanegra et al., 2018 ). Moreover, the recent detection of USUV (RNA in mosquitoes and USUV-specific antibodies in birds) and an undetermined flavivirus highlights the widespread circulation of WNV in this endemic area and its co-circulation with USUV and other flaviviruses ( Bravo-Barriga et al., 2023 ). In the six patients studied in this work, cross-reactive IgG antibodies against USUV and TBEV were detected in all the convalescent sera samples tested, but not in the CSF.…”
Section: Discussionmentioning
confidence: 99%
“…These cases were detected in areas where circulation of WNV and other flaviviruses, such as Usutu (USUV) and Tick-borne encephalitis (TBEV), has been described in birds, horses, and/or dogs ( García-Bocanegra et al., 2018 ; Bravo-Barriga et al., 2021 ; Guerrero-Carvajal et al., 2021 ). Moreover, in 2020, when the WNV human outbreak occurred, USUV RNA was detected in mosquitoes and USUV-specific antibodies were detected in wild birds close to rural and urban areas, which is indicative of an active circulation and represents a public health threat ( Bravo-Barriga et al., 2023 ). In 2021, no WNV human cases or animal outbreaks were reported through the veterinary surveillance system, and in 2022, there were only three equine outbreaks in Badajoz ( Ministry of Agriculture and Fisheries and Food, 2023a ; Ministry of Agriculture and Fisheries and Food, 2023b ).…”
Section: Introductionmentioning
confidence: 99%